Experience in the management of distal third tibia and fibula fractures by interlocking intramedullary nail in Community Based Medical College Hospital - Islam, Md Saiful; Hossain, Md Tufael; Uddin, Md Nasir; Chowdhury, Mamunur Rashid; Hasan, Md Sabbir (Community Based Medical Journal, 2022)
Objective: To determine the effect of interlocking intramedullary nail in treatment of tibia and fibula fractures and analyze its efficacy by clinical and radiological parameters. Methods: From August 2015 to September 2017, in Community Based Medical College Hospital, Orthopedics department, 15 patients with tibia and fibula fractures were managed by open reduction and interlocking nail and each case was followed up for 7 months. The cases were assessed clinically and by radiology. Results: There were 13 males and 2 females involving 10 right legs and 5 left legs. Ages of patients ranged from 17 years to 60 years with mean age 36.13 years and standard deviation 11.813 years. The location of fractures was 1 upper, 2 middle and 12 lower. There was association of 1 fracture femur right side. Conclusion: Use of interlocking intramedullary nail in management of tibia and fibula fractures was good in majority of cases. CBMJ 2021 January: vol. 10 no. 02 P: 91-97